The Effect of Danofloxacine on in vitro Rat Myometrium - Akar, Yasar; Kara, Haki; Servi, Kadir; Yildiz, Hamit (Univ Agriculture, Fac Veterinary Science, 2010)
The aim of this study was to determine the effect of danofloxacine on in vitro rat myometrium. The myometrium (n= 60) obtained from adult female rats. After myometrium showed spontaneous contractions, the contractions were regulated by injecting 0.1mM oxytocin. Then, 5, 10, 20, 40 and 80 mu mol danofloxacine was added to isolated organ bath in 10 min intervals, and frequency, peak amplitude and peak area calculations were recorded. With oxytocin supplementation, frequency, peak amplitude and peak area calculations were determined as 6.7 +/- 1.0, 1874 +/- 107, 1749 +/- 68, respectively. With danofloxacine supplementation, frequency and peak amplitude first increased then slowed down in relation to the dose and the peak area decreased in relation to the dose (P<0.05). In conclusion, by adding danofloxacine to the media after contractions caused by an oxytocin treatment, we observed biphasic activity. The effects of danofloxacine high doses (40 and 80 mu mol) may inhibit both K+ channels and the intracellular-induced mechanism. (c) 2010 PVJ. All rights reserved
Keywords: Danofloxacine; Myometrium; Oxytocin; Rat